Synthesis of Aqueous Suspensions of Zero-Valent Iron Nanoparticles (nZVI) from Plant Extracts: Experimental Study and Numerical Modeling - Michalis Karavasilis; Christos D. Tsakiroglou (Ital Publication, 2019)
Plant extracts were produced from Camellia sinesis (Green Tea) and Punica granatum (pomegranate), and the total concentration of polyphenols was measured in terms of equivalent concentration of Gallic acid by using the Folin-Ciocalteu method. Zero Valent Iron nanoparticles (nZVIs) were synthesized in a semi-batch reactor by mixing a pre-specified volume of plant extract or Gallic Acid solution with an aqueous solution of iron sulfate heptahydrate (FeSO4·7H2O). To monitor the kinetics of nZVI synthesis, the transient responses of solution pH and redox potential (Eh) were recorded with two probes adequately connected with a data acquisition card. The nanoparticles were characterized by a variety of techniques: Dynamic Light Scattering (DLS), ζ-potential, Attenuated Total Reflectance-Fourier Transform Infrared (ATR-FTIR) spectroscopy, Transmission Electron Microscopy (TEM). A kinetic parametric model, based on two parallel single electron transfer (SET) and hydrogen atom transfer (HAT) reactions, was suggested to quantify the dynamics of ferrous ions reduction to zero valence, and its parameters were estimated for each experimental system by matching the transient response of pH. The temporal changes of redox potential during nZVI synthesis were indicative of the reaction progress and agreed with the numerical predictions in semi-quantitative basis. The numerical model enabled us to track the temporal variation of the concentration of iron and polyphenol species, and calculate the yield of ZVI synthesis. The reactivity of nZVIs was assessed by measuring their capacity to reduce hexavalent chromium Cr (VI) in aqueous solutions prepared from potassium dichromate (K2Cr2O7).